Individual choice of menopausal hormone therapy - T V Ovsyannikova; I A Kulikov (IP Berlin A.V., 2016)
The goal of anti-aging menopausal hormone therapy (MHT) lies in maintenance and restoration of the major organs and body systems, thus achieving two main effects: increasing life expectancy and improving its quality, which is fully consistent with the desires of women in perimenopausal and postmenopausal women. MHT started in the menopausal transition period is not only the treatment of early symptoms of menopause, but menopause itself and prevention of late complications. The article discusses the possibility and efficacy of Angeliq® Micro containing reduced doses of estrogen and progestogen (17β-estradiol 0.5 mg + drospirenone 0.25 mg). Indications for its purpose is to maintain moderate to severe hot flashes in postmenopausal women with an intact uterus.